2022
DOI: 10.3390/jcm11113149
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Care for the Older People: An Urgent Need in the Daily Practice of Oncologists

Abstract: Cancer is the most widespread and prominent health issue worldwide and its incidence is only exceeded by cardiovascular diseases [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These patients consist of an extremely varied population of subjects, ranging form fit to frail, characterized by various clinical conditions, few or many comorbidities and different ability to tolerate chemotherapy ( 5 ). The implementation of a multidimensional geriatric assessment (CGA) and accurate tools such as the Geriatric-8 (G8) and the Vulnerable Elders Survey-13 (VES-13) will be able to guide the clinician on a case-by-case basis in his decision-making process ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients consist of an extremely varied population of subjects, ranging form fit to frail, characterized by various clinical conditions, few or many comorbidities and different ability to tolerate chemotherapy ( 5 ). The implementation of a multidimensional geriatric assessment (CGA) and accurate tools such as the Geriatric-8 (G8) and the Vulnerable Elders Survey-13 (VES-13) will be able to guide the clinician on a case-by-case basis in his decision-making process ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a phase II randomized trial has demonstrated that the an intermittent therapy based on anti-EGFRs limits toxicity and produces a long PFS without any detrimental effect on OS ( 17 ). This approach could be particularly attractive in pre-treated older patients, especially among those who require adaptive treatment, as in vulnerable subjects to whom many of them belong anyway ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, patients with poor performace status (PS), loss of autonomy, and various comorbidities are considered to be “frail” patients and they should be excluded from any type of therapy. The majority of older patients, however, fall into a middle range, i.e., that of “vulnerable” subjects, for whom, from time to time, less intensive and adapted therapies could be assigned on a case-by-case basis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%